Developing Academic Achievement in the Course of History on Thon Buri Establishment by using Game-based Learning for Mathayom 2 Room 3 Students, Nongsaeng Wittaya School - Panichaypan, Panadda; Benrahem, Aphisit; Kerdthong, Suthima (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This study aimed to develop a learning activity plan based on game-based learning about the establishment of Thonburi as the capital, to examine students' academic achievement after using the game-based learning technique, and to assess students' satisfaction with the game-based learning technique. The sample group consisted of 39 eight graders, section 3 (Matthayom 2/3) from Nong Saeng Wittaya School, in the first semester of the 2023 academic year, selected through cluster random sampling. The research instruments included 12 learning activity plans, a 30-item multiple-choice academic achievement test, and a 20-item satisfaction scale. The statistical methods used in the study were mean, standard deviation, and dependent t-test. The results of the study were as follows: 1. A total of 12 learning activity plans were developed, 2. A comparison of academic achievement revealed that students' post-test achievement ( = 18.40, S.D. = 1.44) was significantly higher than their pre-test achievement ( = 12.50, S.D. = 2.14) at the 0.05 level, and 3. Students' satisfaction with the game-based learning technique was high ( = 4.50, S.D. = 1.55).